Business Portfolio and IT Strategy Alignment: Enhancing Performance through Digital Innovation at PT Telkom Indonesia - Sihotang, John; Giovani, Randy; Suhendar, Fikry Ramadhan; Komariyah, Imas (Universitas Mercu Buana, 2025)
The telecommunications industry has been undergoing a wave of transformation due to fundamental shifts in consumer behavior, rapid technological innovation, and increasing market competition. For PT Telkom Indonesia, these changes have posed significant challenges, particularly in the Enterprise segment, where performance has declined in recent years.Objectives: This paper analyzes the relationship between business portfolio configuration, B2B IT digital strategy, and business performance at PT Telkom Indonesia, emphasizing the intermediary role that digital innovation plays in linking strategic initiatives to performance achievements.Methodology: Employing a quantitative design, data were drawn from 136 respondents occupying managerial positions in Telkom Indonesia’s business units. The research model was tested using PLS-SEM facilitated by SmartPLS 4.0, aiming to capture both direct linkages and the mediating impact of digital innovation across variables.Finding: The analysis shows that while the structuring of the business portfolio does not significantly enhance business performance, the deployment of B2B IT digital strategy has a notable positive effect. Furthermore, digital innovation critically shapes organizational outcomes by serving as both a direct contributor and a mediator, reinforcing its strategic importance in converting planned initiatives into measurable value.Conclusion: The study reveals that innovation is fundamental to strategic success. Rather than being determined solely by the formulation of business portfolios or digital strategies, Telkom Indonesia’s performance is significantly influenced by the firm's capability to operationalize these strategies through continuous innovation. These insights reinforce the critical need for digital transformation initiatives to fully integrate innovation into strategic execution frameworks.